Adubação com enxofre e coinoculação na cultura da soja: produtividade e qualidade de grãos - Deak, Evandro Ademir (2020)
The nutritional balance of the soil is one of the main factors that affect the grain yield of crops, and it is essential that nutrients are available in the soil at levels above the critical limit established for each group of crops. The nutrient of greatest demand for soybean culture is nitrogen (N). In Brazil soybeans obtain this nutrient mainly through biological nitrogen fixation (FBN), carried out by diazotrophic bacteria, which convert atmospheric nitrogen (N2) into ammonia (NH3 +). This biological process is dependent on favorable conditions in the cultivation environment, highlighting the availability of sulfur (S), one of the essential nutrients for the metabolism of bacterioids. The objective of this research was to evaluate the effect of inoculation and co-inoculation, combined with doses of S, on the productivity and quality of grains, as well as on the physiological quality of soybean seeds. For this, experiments were conducted in the field and in the seed laboratory. Four field experiments were carried out during the 2017/2018 and 2018/2019 crops, two in Santa Maria and two in Augusto Pestana, Rio Grande do Sul, Brazil. The cultivar Nidera 5959 IPRO was used. The experimental design was randomized blocks, and the treatments were distributed in a 3 x 4 factorial, combining three types of inoculation [Control (non-inoculated), inoculation with Bradyrhizobium spp., and co-inoculation with Bradyrhizobium spp. + Azospirillum brasilense] with four doses of S (0, 20, 40 and 60 kg ha-1), supplied via elemental-S (90 % S). In experiments conducted in the field (Article 1), the nodulation of plants, yield components, productivity and grain quality were evaluated. With the seeds harvested from the field experiments of the 2017/2018 crop, two experiments were conducted in the seed laboratory (Article 2), in which the physiological quality of seeds and enzymatic activity of seedlings were evaluated. The main results obtained were that elemental-S is an efficient alternative to make sulfate available to plants, promoting greater nodulation, accumulation of dry mass of plants, productivity and quality of soybeans. In addition, fertilization with elemental-S combined with co-inoculation of parent plants allows the expression of the vigor of its seeds, in addition to promoting the obtaining of seeds with a higher percentage of germination, possibly due to greater nodulation and consequently accumulation of N. Concludes it is believed that fertilization with elemental-S combined with co-inoculation promotes an increase in the quality of soybeans and seeds.